Avaliação da infecção oral pelo vírus EPSTEIN-BARR em candidatos a transplante e em transplantados renais: estudo citopatológico e molecular - Tavares, Débora dos Santos (2008)
Oral hairy leukoplakia is a white lesion caused by Epstein-Barr virus, frequent in the lateral border of the tongue and initially associated with acquired immune deficiency syndrome. Afterwards, several cases in transplant patients were described in the literature, suggesting that it is related to immunosuppression in general. Its diagnosis can be made by detecting the typical cytopathic effects caused by the virus in the epithelial cells through cytopathology, which can also diagnose its subclinical phase. Therefore, considering that about 95% of the world s population has the virus in the serum and that oral hairy leukoplakia is the only replicative lesion in vivo, its diagnosis could be useful in patients with different degrees of immunosuppression, especially in transplant recipients. The aim of this research was to investigate the association in renal transplant recipients infected by Epstein-Barr virus, of immunosuppression with the pattern of epithelial infection, and also demonstrate that variations on those patterns could be used as a laboratorial marker of immunosuppression. The sample consisted of 10 renal transplant candidates, followed up to six months post-transplant (Group 1), 50 renal transplant recipients (Group 2) and 10 healthy individuals (Control Group). They were submitted to oral exam and had material scraped from both sides of the tongue by using an endocervical brush. A sample of saliva from each subject was also taken. Conventional smears were prepared and the brush containing residual material was preserved as the saliva samples, for future analysis by polymerase chain reaction. There were no lesions clinically visible in any of the subjects of this study; however cytopathology diagnosed four (7%) cases of oral hairy leukoplakia, three in the immediate post-transplant period (up to 120 days) and one in the mediate posttransplant period (above 121 days), as also eight (13%) cases of candidiasis in transplant patients (Groups 1 and 2). Only one case of candidiasis was diagnosed before the transplant. There was statistically significant evidence (p<0,05) confirming the hypothesis that OHL occurs more frequently in the immediate post-transplant period. The Epstein-Barr virus was detected in tongue smears samples of 10 (100%)patients from Group 1 and 48 (96%) patients from Group 2. Regarding its presence in saliva, it was detected in samples from 5 (50%) patients of Group 1 and 18 (36%) patients of Group 2. In the Control Group, epithelial and saliva prevalence resembles the results described in the transplant recipients, presenting, respectively, nine cases (90%) and four (40%) cases. Considering that the first six months is the major period of immunosuppression and that the majority of oral hairy leukoplakia cases (replicative pattern) occurred during this period, we concluded that there is an association between immunosuppression and the beginning of the viral replication in transplant recipients, confirming the hypothesis that oral hairy leukoplakia can be used as a laboratorial marker. Nevertheless, other investigations become important to determine why only a few renal transplant patients developed the lesion and if the replicative infection is associated with the future development of lymphoproliferative diseases.